The semantic organization of the sentence in teaching reading specialty texts (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the methodology of work on the specialty text at the level of sentence. Two ways of analysis of the sentence are offered – «from form to sense» and «from sense to form». The first direction is in understanding the sense of the sentence with the help of the model. Depending on the communicative task different speech situations exist in scientific texts, which are expressed by certain language models. The second way «from sense» is in revealing the semantic meaning of the sentence by means of a question. The author offers the following methodology of work: to find the subject and predicate in the sentence; to define the part of speech of the predicate; to set correctly a grammatical question to the main word of the word-combination which follows the predicate; to write down a question; to highlight the predicate in the question; to highlight the subject; to write down a full question and to give a short answer to a question which will be the semantic centre of the sentence.
Keywords: semantic organization of the sentence; structural-semantic model of the sentence; communicative task of the sentence; meaningful speech situation; semantic center of the sentence.